Analisis Perbedaaan CAR Sektoral Sebelum dan Setelah Terpilihnya Trump Menjadi Presiden AS Tahun 2016 (Event Study di Indonesia) - Roseline Mannuela; Fesa Aditiya; Fransiscus Nicholas (Ilmiah Manajemen Bisnis, 2019)
Abstract — In this event study we analyse CAR (cumulative abnormal return) difference from each business sector in Indonesia before and after the US president election, Trump in 2016. We used daily closing price of 498 companies in each business sector listed on the Indonesia Stock Exchange (BEI) as our data for period October to November 2016. A compare sample t-test was used to analyse our data. The results indicate that there are some differences in CAR before and after the event (US president election) in two sectors, the agricultural sector and basic industry & chemicals. This condition shows that Trump’s victory as US president can be categorized as a trigger event that can make the market react. Keywords— Event study, Cumulative abnormal return